Identity blues: the ethnobotany of the indigo dyeing by Landian Yao (Iu Mien) in Yunnan, Southwest China - Shan Li (Journal of Ethnobiology and Ethnomedicine, 2019)
Abstract Background Indigo-dyed textiles have been central to the cultural identity of Landian Yao (literally “blue clothes Yao”) people in Southwest China for centuries, driving a significant local market for naturally dyed indigo cloth. In the past two decades, local indigo production for traditional textiles has declined for several reasons: Firstly, the younger generation of Landian Yao has shifted to using western style jeans and T-shirts. Secondly, due to its labor-intensive nature. In contrast, at a global scale, including in China, there has been a revival of interest in natural indigo use. This is due to a growing awareness in the fashion industry about human and environmental health issues related to synthetic dye production. Ironically, this new awareness comes at a time when traditional knowledge of indigo dyeing is being lost in many places in China, with weaving and use of natural dyes now limited to some remote areas. In this study, we recorded indigo dyeing processes used by Landian Yao people and documented the plant species used for indigo dyeing. Methods Field surveys were conducted to the study area from September 2015 to November 2016, supplemented by follow-up visits in July 2018 and November 2018. We interviewed 46 key informants between 36 and 82 years old who still continued traditional indigo dyeing practices. Most were elderly people. Semi-structured interviews were used. During the field study, we kept a detailed account of the methods used by Landian Yao dyers. The data were then analyzed by using utilization frequency to determine the best traditional recipe of indigo dye extraction. All the specimens of documented species were collected and deposited at the herbarium of Kunming Institute of Botany. Results Our results showed that indigo dyeing was divided into two main steps: (1) indigo pigment extraction and (2) dyeing cloth. The general procedures of indigo dye extraction included building or buying a dye vat, fermentation, removal of the leaves of indigo producing plant species, addition of lime, oxygenation, followed by collection, and the storage of the indigo paste. The procedures of dyeing cloth included preparing the dye solutions, dyeing cloth, washing, and air drying. It is notable that Landian Yao dyers formerly only performed the dyeing process on the goat days in the lunar calendar from June to October. After comparing the range of local indigo extraction methods, our results showed that the following was best of these traditional recipes: a indigo-yielding plant material to tap water ratio of 30 kg: 200 l, lime 3 kg, a fermentation time of 2–3 d, aeration by agitation for up to 60 min, and a precipitation time of 2–3 h. Our results show that 17 plant species in 11 families were recorded in the indigo dyeing process. With the exception of the indigo sources, only Dioscorea cirrhosa Lour. and Artemisia argyi H.Lév. & Vaniot were previously recorded in dyeing processes. Other species given in this paper are recorded for the first time in terms of their use in the indigo dyeing process. In the study area, Landian Yao men were in charge of indigo dye extraction, and the women were responsible for dyeing cloth. Conclusions The Landian Yao has completely mastered the traditional indigo dyeing craft and are one of the well-deserved identity blues. Indigo production from plants using traditional methods is a slow process compared to synthetic dyes and is not suitable for modern and rapid industrial production. Therefore, our study records the detailed information of traditional indigo dyeing to protect and inherit it. Strobilanthes cusia (Nees) Kuntze is the main indigo source in Landian Yao that is widely used in the world and can be commercially exploited as an indigo plant. For commercial and environment benefits, we suggest that producing natural indigo for the commercial market is a good choice.